To study wear characteristics of cryogenically treated T42 high speed steel - Bandewar, Prof. Ashish; Mathapat, Prof. Nagesh; Kadam, Prof. Amol; Kazi, Prof. Juned (IJRDO - Journal of Applied Management Science, 2016)
The word, “cryogenics” is taken from two Greek words - “kryos” Which means cold or freezing, &“genes” meaning born or generated. Technologically, it means the study & use of materials (or otherrequirements) at very low temperatures. In general cryogenic treatment consists of slow cooling alreadyheat treated parts to approximately -1960 C, holding at low temperature up to prescribed period,reheating without thermal shocks to room temperature & reheat to a moderately elevated temperature(150 to 3150 C) for about 1 or 2 hours, to “temper” the part for the stated purpose of reducing itsbrittleness. In this study cryogenic treatment is performed on AISI T42 HSS material & its wearcharacteristics are studied. Test of treated & untreated samples is taken on pin on disc wear testingmachine at different load & RPM. The wear of the sample is measured. The wear resistance of thesamples is also measured by weight loss method. The results are tabulated. An experimental effort toevaluate tool wear improvement by cryogenic treatment is the outcome of this study.